The need for a fundamental shift in the Saudi education system: Implementing the Saudi Arabian economic vision 2030. (May 2020) - Allmnakrah, Alhasan; Evers, Colin
To put Saudi's Economic Vision 2030 (or Vision 2030) into practice, Saudi Arabia has to reform its education system. To this end, King Abdullah's Education Development Project (hereafter the Tatweer project (Note: Tatweer, as it is known in Arabic)) of 2007–2013 has mandated an educational reform package, which focuses on a broad range of improvements, including enhancing schools' teaching methods and strategies. Hence, this paper argues that to diversify its economy and income away from a strictly oil-producing export country, Saudi Arabia requires an educated citizenry, trained in several disciplines, and students who have the necessary skills for progressing toward a knowledge-based economy. To achieve this, in-service and preservice teachers need to be trained in innovative ways, including listening to their voices and assessing what Saudi teachers require in order to play a positive role in contributing to the achievement the goals outlined in the Vision 2030. This research paper, hence, aims to shed some light into the implantation of Saudi 2030 vision and its direct link to in-service and preservice teachers who must be equipped with the right necessary critical teaching tools. The paper sees teacher voices, teacher training, and the development of strategies such as critical thinking as being essential for future success toward a shift in the Saudi education system vis-à-vis Saudi 2030 vision.